Validation of Risk Scoring Systems in Ursodeoxycholic Acid-Treated Patients With Primary Biliary Cholangitis. - Efe, Cumali; Tascilar, Koray; Henriksson, Ida; Lytvyak, Ellina; Alalkim, Fatema; Trivedi, Hirsh; Eren, Fatih; Eliasson, Johanna; Beretta-Piccoli, Benedetta Terziroli; Fischer, Janett; Caliskan, Ali Riza; Chayanupatkul, Maneerat; et al. (American Journal of Gastroenterology, 2019)
INTRODUCTION: Risk stratification based on biochemical variables is a useful tool for monitoring ursodeoxycholic acid (UDCA)-treated patients with primary biliary cholangitis (PBC). Several UDCA response criteria and scoring systems have been proposed for risk prediction in PBC, but these have not been validated in large external cohorts. METHODS: We performed a study on data of 1746 UDCA-treated patients with PBC from 25 centers in Europe, United States, and Canada. The prognostic performance of the risk scoring systems (GLOBE and UK-PBC) and the UDCA response criteria (Barcelona, Paris I, Paris II, Rotterdam, and Toronto) were evaluated. We regarded cirrhosis-related complications (ascites, variceal bleeding, and/or hepatic encephalopathy) as clinical end points. RESULTS: A total of 171 patients reached a clinical end point during a median 7 years (range 1-16 years) of follow-up. The 5-, 10- and 15-year adverse outcome-free survivals were 95%, 85%, and 77%. The GLOBE and UK-PBC scores predicted cirrhosis-related complications better than the UDCA response criteria. The hazard ratio (HR) for a 1 standard deviation increase was HR 5.05 (95% confidence interval (CI): 4.43-5.74, P < 0.001) for the GLOBE score and HR 3.39 (95% CI: 3.10-3.72, P < 0.001) for the UK-PBC score. Overall, the GLOBE and UK-PBC risk scores showed similar and excellent prognostic performance (C-statistic, 0.93; 95% CI: 0.91%-95% vs 0.94; 95% CI: 0.91%-0.96%). DISCUSSION: In our international, multicenter PBC cohort, the GLOBE and UK-PBC risk scoring systems were good predictors of future cirrhosis-related complications.
EVALuna2:424198